An assessment of high human population density and its impacts on land resources in Moshi district council, Tanzania - Alphonce, Emmanuel (Mzumbe Unversity, 2024)
A dissertation submitted in partial fulfilment of the requirements for the award of the Degree of Master of Science in Environmental Management (MSc. EM) of the Mzumbe University